Physical function in UK adults with osteogenesis imperfecta: a cross-sectional analysis of the RUDY study - Orlando, G; Pinedo-Villanueva, R; Reeves, ND; Javaid, MK; Ireland, A (Springer, 2020)
Summary We describe the physical function in adults with osteogenesis imperfecta (OI) and explored clinical and non-clinical factors related to its impairment. Our data showed that physical dysfunction is a common feature of adults with OI, varying by OI severity, and mediated by the presence and quality of pain and fatigue symptoms.